A randomised controlled trial of a complex intervention to reduce children’s exposure to secondhand smoke in the home - Ratschen, Elena; Thorley, Rebecca; Jones, Laura L.; Opazo Breton, Magdalena; Cook, Juliette; McNeill, Ann; Britton, John; Coleman, Tim; Lewis, Sarah (BMJ Publishing Group, 2018)
Objectives: Exposing children to secondhand tobacco smoke (SHS) causes significant harm and occurs predominantly through smoking by caregivers in the family home. We report a trial of a complex intervention designed to reduce secondhand smoke exposure of children whose primary caregiver feels unable or unwilling to quit smoking.